New developments in economic education - Mixon, Franklin Graves, 1965-; Cebula, Richard J. (Cheltenham, UK : Edward Elgar, 2014)
This volume is a welcome addition to an ever growing body of work in economic education. A wide range of content areas are covered throughout, with dedicated chapters of the Coase theorem and tax evasion.
Includes bibliographical references (pages 224-245) and index.
Keywords: Economics -- Study and teaching (Higher)